TER TINJAUAN TEKNIS DAN EKONOMIS PENANGANAN PERSIMPANGAN JALAN (STUDI KASUS JL. KAHARUDIN NASUTION – JL. PASIR PUTIH KOTA PEKANBARU) - Rafli Arie Pradhana; Ari Sandhyavitri; Muhammad Ikhsan; Leo Sentosa; Muhamad Yusa; Ferry Fatnanta (Racic : Rab Construction Research, 2026)
Pekanbaru City, as the provincial capital, has experienced significant population growth, resulting in increased mobility and severe traffic congestion, particularly at urban intersections. This study evaluates the performance and feasibility of management alternatives for the problematic Kaharudin Nasution-Pasir Putih intersection. The analysis uses the Indonesian Road Capacity Guidelines (PKJI 2023) for technical performance assessment and the LAPI ITB 1996 method for economic analysis, focusing on Vehicle Operating Costs (VOC), Benefit Cost Ratio (BCR), and Net Present Value (NPV) for the short (5 years), medium (10 years), and long (15 years) terms. The existing condition indicates a poor Level of Service (LOS D) with a Degree of Saturation (DS) of 0.76. Four alternatives were evaluated: Traffic Light Optimization, Road Widening, Adding 1 Lane, and Construction of an Overpass. The results indicate that Alternatives 1, 2, and 3 offer only short- to medium-term improvements. The construction of the Flyover (Alternative 4) is the only feasible long-term solution (15 years), proven to be economically feasible with BCR and NPV values of 1.46 and 55.6 billion rupiah, in the 10th year 3.19 and 270.3 billion rupiah, and in the 15th year 4.79 and 482.3 billion rupiah. which means the benefit value is greater than the costs incurred, so that the construction of the flyover is economically feasible to be implemented to minimize the increasing financial losses due to traffic delays.